The immunophenotype of amniotic fluid leukocytes in normal and complicated pregnancies. (3rd March 2018) - Gomez‐Lopez, Nardhy; Romero, Roberto; Xu, Yi; Miller, Derek; Leng, Yaozhu; Panaitescu, Bogdan; Silva, Pablo; Faro, Jonathan; Alhousseini, Ali; Gill, Navleen; Hassan, Sonia S; Hsu, Chaur‐Dong
Abstract : Problem: The immune cellular composition of amniotic fluid is poorly understood. Herein, we determined: 1) the immunophenotype of amniotic fluid immune cells during the second and third trimester in the absence of intra‐amniotic infection/inflammation; 2) whether amniotic fluid T cells and ILCs display different phenotypical characteristics to that of peripheral cells; and 3) whether the amniotic fluid immune cells are altered in women with intra‐amniotic infection/inflammation. Method of Study: Amniotic fluid samples (n = 57) were collected from 15 to 40 weeks of gestation in women without intra‐amniotic infection/inflammation. Samples from women with intra‐amniotic infection/inflammation were also included (n = 9). Peripheral blood mononuclear cells from healthy adults were used as controls (n = 3). Immunophenotyping was performed using flow cytometry. Results: In the absence of intra‐amniotic infection/inflammation, the amniotic fluid contained several immune cell populations between 15 and 40 weeks. Among these immune cells: (i) T cells and ILCs were greater than B cells and natural killer (NK) cells between 15 and 30 weeks; (ii) T cells were most abundant between 15 and 30 weeks; (iii) ILCs were most abundant between 15 and 20 weeks; (iv) B cells were scarce between 15 and 20 weeks; yet, they increased and were constant after 20 weeks; (v) NK cells were greater between 15 and 30 weeks than at term; (vi) ILCs expressed high levels of RORγt, CD161, and CD103 (ie, group 3 ILCs); (vii) T cells expressed high levels of RORγt; (viii) neutrophils increased as gestation progressed; and (ix) monocytes/macrophages emerged after 20 weeks and remained constant until term. All of the amniotic fluid immune cells, except ILCs, were increased in the presence of intra‐amniotic infection/inflammation. Conclusion: The amniotic fluid harbors a diverse immune cellular composition during normal and complicated pregnancies. Abstract : The immunophenotype of amniotic fluid leukocytes throughout the second and third trimester in the absence of intra‐amniotic infection/inflammation. Flow cytometry analysis of amniotic fluid leukocytes is shown in t‐SNE plots.